Implementation of Technology and Digital Literacy in the Context of Continuous Improvement: A Case Study of Education Quality Management at SMK Negeri 4 Samarinda - Ayu, Dinda; Suharmi, Suharmi; Wulandari, Yuli; Azainil, Azainil; Komariyah, Laili (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Digital transformation in education has become a global phenomenon that is changing the way schools learn and manage. This study examines the implementation of technology and digital literacy in the context of continuous improvement at SMK Negeri 4 Samarinda, with the aim of improving the quality of education. This study uses a qualitative case study approach through in-depth interviews, participatory observations, and document analysis. The results of the study show that SMK Negeri 4 Samarinda has integrated various digital platforms in the learning process, such as Google Classroom, Moodle, and the school's internal LMS, as well as interactive media such as videos, animations, and simulations. The school also implements a digital-based Internal Quality Assurance System (SPMI) to document and manage the education quality assurance process. In addition, schools use data-based management to improve the quality of learning, by relying on data on student learning outcomes, attendance, and teacher performance evaluation. The implementation of the flexible and student-based Independent Curriculum, as well as the use of digital technology in learning, has a significant impact on improving the quality of learning and students' skills. Technology-based evaluation and strengthening technical and soft skills also support students' readiness to enter the digitalized world of work. This research contributes to understanding how technology and digital literacy can strengthen continuous improvement in education quality management in vocational schools, as well as become a model for vocational schools in the era of the Industrial Revolution 4.0.